Pendekatan Pendidikan Islam Berbasis Teknologi dalam Pembelajaran Mata Pelajaran Agama Islam di Sekolah Dasar - Wahidin; Edy Susanto (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This research is expected to provide valuable insights into the use of technology in Islamic learning in elementary schools, to help improve the quality of Islamic learning and provide new alternatives for teachers and students. The research method that can be used to examine the Technology-Based Islamic Education Approach to Learning Islamic Religious Subjects is qualitative. Qualitative research methods aim to understand social phenomena in depth, through data analysis that is descriptive and interpretive. Based on research that has been conducted, technology-based Islamic education approaches in learning Islamic religious subjects in elementary schools have an important role in increasing student interest and motivation, increasing students' understanding of learning materials, increasing students' creativity and independence in learning, and increasing learning efficiency and effectiveness. Some technology-based Islamic education approaches that can be used include game-based learning or educational games, the use of multimedia, distance learning, the use of learning applications, and the exploration of digital learning resources.